Răspuns :
a = (3x - 2)(x + 1) - 3(x - 1)²= (3x² + 3x -2x -2) -3 (x²-2x+1) = (3x² + x - 2) - 3x² + 6x -3 = 7x - 5 deci a = 7x - 5
a)
a = 2
2 = 7x - 5
2 + 5 = 7x
7 = 7x
x = 1
b)a² =81 dar a = 7x - 5
(7x -5 )² = 81
7x - 5 = 9
7x =9 +5
7x = 14
x = 2
c)
IaI = 1 dar a = 7x - 5
I7x - 5 I =1
IxI ={x, x≥0} si IxI ={-x, x<0}
deci
1. I7x - 5 I =1 pentru x≥0, ⇒ 7x - 5 = 1⇒ 7x = 1 + 5⇒x = 6/7
2.1. I7x - 5 I =1 pentru x<0, ⇒ 7x - 5 = - 1⇒ 7x = - 1 + 5⇒x = 4/7
S = { 6/7 ; 4/7 }
d)
a -16 = 0 dar a = 7x - 5
7x - 5 -16 = 0
7x = 21
x = 3